Developing nondestructive techniques for managing conflicts between fisheries and double‐crested cormorant colonies. (15th September 2015) - Suzuki, Yasuko; Roby, Daniel D.; Lyons, Donald E.; Courtot, Karen N.; Collis, Ken
ABSTRACT: Double‐crested cormorants ( Phalacrocorax auritus ) have been identified as the source of significant mortality to juvenile salmonids ( Oncorhynchus spp.) in the Columbia River Basin. Management plans for reducing the size of a large colony on East Sand Island (OR, USA) in the Columbia River estuary are currently being developed. We evaluated habitat enhancement and social attraction as nondestructive techniques for managing cormorant nesting colonies during 2004–2007. We tested these techniques on unoccupied plots adjacent to the East Sand Island cormorant colony. Cormorants quickly colonized these plots and successfully raised young. Cormorants also were attracted to nest and raised young on similar plots at 2 islands approximately 25 km from East Sand Island; 1 island had a history of successful cormorant nesting whereas the other was a site where cormorants had previously nested unsuccessfully. On a third island with no history of cormorant nesting or nesting attempts, these techniques were unsuccessful at attracting cormorants to nest. Our results suggest that some important factors influencing attraction of nesting cormorants using these techniques include history of cormorant nesting, disturbance, and presence of breeding cormorants nearby. These techniques may be effective in redistributing nesting cormorants away from areas where fish stocks of conservation concern are susceptible to predation, especially if sites with a recent history of cormorant nesting are available within their foraging or dispersal range. Published 2015. Wiley Periodicals, Inc. This article is a US Government work and, as such, is in the public domain in the United States of America.